Znaczenie terapii zajęciowej w domach pomocy społecznej = The importance of occupational therapy in social welfare homes - Pietkun, Katarzyna; Siminska, Joanna; Ogurskowski, Karol; Nowacka, Krystyna (Journal of Education, Health and Sport, 2015)
Pietkun Katarzyna, Siminska Joanna, Ogurskowski Karol, Nowacka Krystyna. Znaczenie terapii zajęciowej w domach pomocy społecznej = The importance of occupational therapy in social welfare homes. Journal of Education, Health and Sport. 2015;5(4):195-204. ISSN 2391-8306. DOI: 10.5281/zenodo.16768 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A195-204 https://pbn.nauka.gov.pl/works/554265 http://dx.doi.org/10.5281/zenodo.16768 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.02.2015. Revised 27.03.2015. Accepted: 05.04.2015. ZNACZENIE TERAPII ZAJĘCIOWEJ W DOMACH POMOCY SPOŁECZNEJ The importance of occupational therapy in social welfare homes Pietkun Katarzyna, Siminska Joanna, Ogurskowski Karol, Nowacka Krystyna Katedra i Klinika Rehabilitacjii Collegium Medicum UMK w Bydgoszczy Streszczenie Terapia zajęciowa łączy zarówno rehabilitację medyczną jak i społeczną, jest ona także formą, która uzupełnia rehabilitację psychologiczną i fizjoterapię. Terapia zajęciowa oddziałuje na aktywność psychiczną ale także w dużym stopniu pozwala rozwijać zdolności manualne. Nagły rozwój terapii zajęciowej datuje się na lata 90 ubiegłego wieku, gdzie stała się ona bardzo pomocna w placówkach o różnych profilach, a w szczególności w domach pomocy społecznej, szkołach integracyjnych itp. Terapia zajęciowa na za zadanie uświadomienie uczestnikom, ze proste zadanie takie jak: codzienna praca, zabawa zwykłe zadania mają wpływ na cały proces terapeutyczny. Odgrywa to szczególną rolę w procesie profilaktyki zdrowotnej, promowaniu współuczestnictwa w życiu społecznym, poprawie kontaktów interpersonalnych osób z różnym stopniem niepełnosprawności. Słowa kluczowe: terapia zajęciowa, rehabilitacja społeczna, dom pomocy społecznej. Abstract Occupational therapy combines both social and medical rehabilitation, she is also a form of, which complements the psychological rehabilitation and physiotherapy. Occupational therapy to mental activity, but also to a large extent to develop manual dexterity. Sudden development of occupational therapy dates back to the mid-1990s of the last century, where it has become very helpful in schools with different profiles, and, in particular, social welfare homes, schools, integration, etc. Occupational therapy on the task of becoming aware of the participants, with a simple task such as daily work, fun simple tasks have an impact on the therapeutic process. It plays a particular role in the process of health prevention, promotion of participation in social life, the improvement of interpersonal contacts of people with varying degrees of disability. Keywords: occupational therapy, social rehabilitation, social welfare home.